2022
DOI: 10.1038/s42003-022-04176-0
|View full text |Cite
|
Sign up to set email alerts
|

Tcf12 is required to sustain myogenic genes synergism with MyoD by remodelling the chromatin landscape

Abstract: Muscle stem cells (MuSCs) are essential for skeletal muscle development and regeneration, ensuring muscle integrity and normal function. The myogenic proliferation and differentiation of MuSCs are orchestrated by a cascade of transcription factors. In this study, we elucidate the specific role of transcription factor 12 (Tcf12) in muscle development and regeneration based on loss-of-function studies. Muscle-specific deletion of Tcf12 cause muscle weight loss owing to the reduction of myofiber size during devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 70 publications
2
7
0
Order By: Relevance
“…We observed that rs4361970 was most accessible in E8.5 spinal cord cells ( Figure 4D ). We also found rs2733330 region at Tcf12 locus ( Cao et al, 2010 ; Ke et al, 2021 ; Wang et al, 2022 ). Tcf12 bind to the E-box regions of Myod and Myog, contributing to SMP ( Parker et al, 2006 ).…”
Section: Resultssupporting
confidence: 62%
“…We observed that rs4361970 was most accessible in E8.5 spinal cord cells ( Figure 4D ). We also found rs2733330 region at Tcf12 locus ( Cao et al, 2010 ; Ke et al, 2021 ; Wang et al, 2022 ). Tcf12 bind to the E-box regions of Myod and Myog, contributing to SMP ( Parker et al, 2006 ).…”
Section: Resultssupporting
confidence: 62%
“…For example, highly activated CX muscle enhancers were enriched with the TFs MEF2D , MEF2A , MEF2C , FOSL2 and BACH2 , which showed the potential target genes like UTRN , NEB , SGCE , TCF12 and MKX . Among these potentially targeted UTRN and NEB genes associated with certain muscle‐related diseases (Deconinck et al., 1997; Ranu et al., 2022), TCF12 was reported to regulate muscle development (Wang et al., 2022). In addition, highly activated CX adipose enhancers were enriched with the TFs FOSL2 , ATF3 , JUNB , SIX2 and MEF2D .…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, PPARG, LPIN1 and CEBPB could influence adipocyte differentiation, lipid metabolism and glucose homeostasis in adipose tissue (Barroso et al, 1999;Park et al, 2010;Reue & Zhang, 2008). TCF12 and PPARG have already been reported as key genes related to muscle development and fatty acid formation (Barroso et al, 1999;Wang et al, 2022). Combining the important role of TFs enriched in the highly activated CX muscle enhancers or highly activated CX fat enhancers and their potential target genes, the muscle and fat tissue function associated regulatory network revealed by this study can provide theoretical support for further study of pork quality.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the amyloid beta precursor protein binding family A member 3 ( APBA3 ) gene, situated in the region from 21.44 Mb to 21.45 Mb, has been linked to ovarian hyperstimulation for in vitro fertilization in women [ 78 ]. Furthermore, the transcription factor 12 ( TCF12 ) gene, found between 53.05 Mb and 53.52 Mb, has been observed to play a role in muscle development and regeneration, as indicated by loss-of-function studies, and is important in regulating cell growth and differentiation during embryonic development [ 79 ].…”
Section: Discussionmentioning
confidence: 99%